Stepping up to genome scan allows stock differentiation in the worldwide distributed blue shark Prionace glauca. Issue 5 (25th December 2022) - Nikolic, Natacha; Devloo‐Delva, Floriaan; Bailleul, Diane; Noskova, Ekaterina; Rougeux, Clément; Delord, Chrystelle; Borsa, Philippe; Liautard‐Haag, Cathy; Hassan, Mohamad; Marie, Amandine D.; Feutry, Pierre; Grewe, Peter; et al.
Abstract: The blue shark Prionace glauca is a top predator with one of the widest geographical distributions of any shark species. It is classified as Critically Endangered in the Mediterranean Sea, and Near Threatened globally. Previous genetic studies did not reject the null hypothesis of a single global population. The blue shark was proposed as a possible archetype of the "grey zone of population differentiation, " coined to designate cases where population structure may be too recent or too faint to be detected using a limited set of markers. Here, blue shark samples collected throughout its global range were sequenced using a specific RAD method (DArTseq), which recovered 37, 655 genome‐wide single nucleotide polymorphisms (SNPs). Two main groups emerged, with Mediterranean Sea and northern Atlantic samples (Northern population) differentiated significantly from the Indo‐west Pacific samples (Southern population). Significant pairwise F ST values indicated further genetic differentiation within the Atlantic Ocean, and between the Atlantic Ocean and the Mediterranean Sea. Reconstruction of recent demographic history suggested divergence between Northern and Southern populations occurred about 500 generations ago and revealed a drastic reduction in effective population size from a large ancestral population. Our results illustrate the power of genome scans to detect population structure and reconstruct demographic history in highly migratory marine species. Given that the management plans of the blue shark (targeted or bycatch) fisheries currently assume panmictic regional stocks, we strongly recommend that the results presented here be considered in future stock assessments and conservation strategies.